2023
DOI: 10.3390/cells12162087
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Disease-like Pathological Features in the Dorsal Hippocampus of Wild-Type Rats Subjected to Methionine-Diet-Evoked Mild Hyperhomocysteinaemia

Maria Kovalska,
Petra Hnilicova,
Dagmar Kalenska
et al.

Abstract: Multifactorial interactions, including nutritional state, likely participate in neurodegeneration’s pathogenesis and evolution. Dysregulation in methionine (Met) metabolism could lead to the development of hyperhomocysteinaemia (hHcy), playing an important role in neuronal dysfunction, which could potentially lead to the development of Alzheimer’s disease (AD)-like pathological features. This study combines proton magnetic resonance spectroscopy (1H MRS) with immunohistochemical analysis to examine changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
(194 reference statements)
0
3
0
Order By: Relevance
“…Moreover, homocysteine can activate microglia, leading to neuroinflammation, another mechanism contributing to neurodegeneration [342,363]. Besides, there are indications that high methionine levels might influence the formation and aggregation of beta-amyloid plaques, a hallmark of Alzheimer's disease, further suggesting a link between methionine-rich diets and neurodegenerative processes [363][364][365][366][367][368][369][370][371][372][373][374][375]. Elevated homocysteine levels have also been associated with increased tau hyperphosphorylation, a hallmark of Alzheimer's disease [176,370].…”
Section: Neuronal Damage and Neurodegenerative Processes Induced By H...mentioning
confidence: 99%
“…Moreover, homocysteine can activate microglia, leading to neuroinflammation, another mechanism contributing to neurodegeneration [342,363]. Besides, there are indications that high methionine levels might influence the formation and aggregation of beta-amyloid plaques, a hallmark of Alzheimer's disease, further suggesting a link between methionine-rich diets and neurodegenerative processes [363][364][365][366][367][368][369][370][371][372][373][374][375]. Elevated homocysteine levels have also been associated with increased tau hyperphosphorylation, a hallmark of Alzheimer's disease [176,370].…”
Section: Neuronal Damage and Neurodegenerative Processes Induced By H...mentioning
confidence: 99%
“…Although the triggers, underlying mechanisms, and effective treatments of AD are still unclear, recent studies have shown that dietary interventions may be potential treatment strategies (Valls-Pedret et al, 2015 ). Dietary restriction during adulthood (DR; reducing calorie intake while maintaining micronutrient levels) reduces the risk of AD (Nuru et al, 2018 ; Kovalska et al, 2023 ). Age-related impairments in learning, memory, and motor function were observed to improve in rodents undergoing dietary restriction, however the mechanics remain unclear (Xu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…High methionine diet has been proven to induce AD-like symptoms (Pi et al, 2021 ). As a dietary intervention, methionine restriction has been reported to alleviate AD, but the molecular mechanisms remain unclear (Alachkar et al, 2022 ; Kovalska et al, 2023 ; Xi et al, 2023 ). Therefore, it is of great significance to explore the specific mechanisms, by which methionine is involved in the pathogenesis of AD.…”
Section: Introductionmentioning
confidence: 99%